Changing Pattern of Rural Life and Livelihood: An Ethnographic Investigation - Bhatta, Megh Vilas; Kharel, Suman (Nepalese Journal of Development and Rural Studies, 2018)
The changing livelihood is an unstoppable phenomenon of the contemporary world at the present era. In the due course of social development, changes have been noticed and the social transformation has become an inevitable process. In the study upon the Aarukharka village, various external interventions like modernity, urbanization and globalization have been found to be the causative factors of ongoing changes in the pattern of people’s life and livelihood strategies in the studied community. A qualitative approach backed up by the ethnographic method was applied while various tools and techniques such as elongated stay with the community people followed by key informant interview (KII) and interaction with the participants, observation and discussion were used to gather data. Although change is a dynamic and a common phenomenon, this study implies that the change in the livelihood pattern of the target community is because of the increasing influence of the above mentioned interventions. The finding indicates that livelihood strategies are changing rapidly in the rural areas of Nepal. Despite the fact that the agriculture with livestock farming was an important traditional source of livelihood in the past, the roles of non-agricultural sectors have become significant for livelihood sustaining in the rural communities of Nepal in the present days.